Reconstructing the Regulation of Non-Taxable Acquisition Value in Land and Building Rights Acquisition Duty for Inheritance in Indonesia - Putri Langgeng Sari; Tunggul Anshari Setia Negara; Istislam Istislam (State Islamic University of North Sumatra Indonesia, 2026)
This article examines the legal ambiguity surrounding the Acquisition Value of Non-Taxable Tax Objects (NPOPTKP) in the Land and Building Rights Acquisition Duty (BPHTB) on inheritance in Indonesia. The problem arises from the absence of a clear mechanism for applying NPOPTKP when inherited land or buildings are received by multiple heirs. Article 46 paragraph (6) of Law Number 1 of 2022 provides a special threshold for inheritance and testamentary grants within a direct family line and between spouses, but does not clarify whether the reduction applies to each heir, only one heir, or heirs who have previously used NPOPTKP. This normative legal research employs statutory and conceptual approaches by examining the UUHKPD, inheritance law, tax principles, legal certainty, legal protection, legal interpretation, and legislative theory. The findings indicate that the current regulation creates uncertainty in tax calculations, unequal fiscal burdens, delays in land registration, and inconsistent practices among local tax authorities. NPOPTKP in inheritance-based BPHTB should therefore be reconstructed through a subject-based, proportional, recorded, and harmonized model. Each heir must be recognized as an individual taxpayer, receive NPOPTKP according to their inheritance share, and have its use recorded in an integrated regional tax system. This model strengthens legal certainty and protection for heirs while preserving local government fiscal interests.